Management of Stored Grain Insects, Part III - Sloderbeck, Phillip E.; Subramanyam, Bhadriraju; Higgins, Randall A. (My University, 2002)
This publication helps producers manage stored grain and avoid pest problems.
MF917_2002_07
Keywords: MF917; Insects; Crops; Equipment and structures; MF